Dynamics of Urbanization and Ecosystem Services Provision - Congedo, Luca; Assennato, Francesca; Munafò, Michele (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on monitoring and analysis of the relationship between urbanization and ecosystem services on the different scales. The use of innovative technologies for land cover change monitoring, ecosystem services modeling and mapping, innovation in land use planning, and which highlight the potential of technologies to tackle challenges such as sustainability of urbanization, climate change adaptation, sustainable land management, and food security are of particular interest.